Effects of atrazine, isoproturon and diuron on glutathone metabolism of Saccharomyces cerevisiae - Alves-Pereira, I (2014)
Under normoxic conditions, living organisms can very efficiently prevent reactive oxygen (ROS) accumulation and attenuate oxidative damages, using various defensive strategies such as those involving the peptide glutathione. However, sudden exposure of eukaryotic cells to xenobiotic as herbicides may cause a redox imbalance of the cell, causing oxidative stress. The yeast Saccharomyces cerevisiae is a promising unicellular eukaryotic organism for the toxicological evaluation of xenobiotic as herbicides, because its cellular structure and functional organization have many similarities to those of higher-level organisms. However, the toxicity of phenylureas and triazines herbicides in yeast is still poorly understood. These photosystem II inhibitors herbicides are mainly used in agricultural applications for selective control of germinating grass and broad-leaved weeds in many crops (e.g. cereals). Diuron is also employed for total weed control on non-cultivated areas as maintenance of roads, railways and parks. On the other hand, atrazine (ATZ), diuron (DIU) and isoproturon (IPU) are the most used herbicides in Europe that are often found in contaminated groundwater, surface water, and effluents of wastewater treatment plants. Consequently, the main purpose of this study was to compare the effects of ATZ, DIU and IPU on yeast cell growth and glutathione cycle enzymes.